Effects of educational mismatch on wages across industry and occupations: sectoral comparison - Lasso-de-la-Vega, Elena; Sánchez-Ollero, José Luis; García-Pozo, Alejandro (Emerald, 2023)
Purpose This study conducts a comparative analysis of the impact of educational mismatch on Spanish wages. This paper aims to focus on the industrial, construction and service sectors at three levels of disaggregation: sector, occupation and gender. Design/methodology/approach The over-education, required education and under-education (ORU model), was applied to data from the 2018 Spanish Wages Structure Survey conducted by the Spanish National Statistics Institute. Findings The industrial sector is the one that best manages over-education by offering the highest returns to each year of over-education. It is also the sector that most values the education of women, particularly those in highly qualified positions. Originality/value This study compares the wage effects of educational mismatch in the service, industry and construction sectors. Previous literature has ignored the latter sectors in this field of study, but the results of the present study show that the industrial sectors significantly value and remunerates worker education. Therefore, it may be worthy to focus certain economic and social policies on this sector, to contribute to reducing gender wage gaps and gender employment discrimination in the economy.
Keywords: Mercado de trabajo; Educación y empleo; Human capital; Wage differentials; Educational mismatch; Gender; Sectors